An empirical case study of international strategic alliances in Malaysia - Abdul Ghani, Ahmad Bashawir; Ishak, Mohamed Mustafa; Tull, Malcolm (Centre for Promoting Ideas (CPI), USA, 2011)
The initial objective of the research project reported in this paper was to examine the strategic approaches, processes and factors involved when foreign companies make its foray into an Asian market. The study focused on the South-East Asian Market, specifically Malaysia, given both the regions and the country’s growing importance in international trade. The theoretical underpinnings of this paper focus on foreign investment, modes of entry, export marketing, strategic alliances, investment criteria, firm characteristics, international business, external factors, host and home country factors, and Asian culture and management.